(untitled) (Vietnam Journal of Community Medicine, 2021)
Objective: Evaluation of job satisfaction of medical staff at National Otorhinorarynology Hospital of Vietnam, 2019. Methods: Design a cross-sectional descriptive study, interview 306 health workers according to a set of prepared questionnaires built on the two-factor theory of Ferederick Herzberg. Results: The overall satisfaction rate of medical staff is high, reaching 95.4%. health workers are most satisfied with their relationship with colleagues 93.5%, followed by learning and development opportunities 91.8%, income and policies, both are 88.9%, on benefits 88.6%, on supervisor supervision 88.2% and finally on working conditions 82.7%. Logistic regression analysis showed that the overall satisfaction rate in the married group was lower than the single group (OR=0.75; 95%CI: 0.42-0.99; p<0.05); higher in the group of intermediate and college degrees than in the university group (OR=1.63; 95%CI: 1.12-2.85; p<0.001); in the group working for more than 15 years was higher than that of the group under 5 years (OR=1.66; 95%CI: 1.06-2.23; p<0.05). Conclusion: Effective management in the hospital in the context of financial autonomy helps the satisfaction rate of health workers to be high. It is necessary to improve the infrastructure in some faculties and focus on the group of medical staff with short working years in human resources.